Dynamic contrast-enhanced magnetic resonance imaging studies in preclinical settings and beyond - Septian Hartono (2014)
Dynamic Contrast-Enhanced Magnetic Resonance Imaging (DCE-MRI) with tracer kinetic modeling has been proposed as a biomarker for assessment of tumor angiogenesis in clinical trials. In this work, we developed and implemented a high spatial and temporal resolution (2 s) DCE-MRI protocol for small animal preclinical studies. Microcirculatory parameters derived were validated with corresponding immunohistochemistry staining of murine human xenografts. Results show that the technique is potentially applicable as a biomarker for pre-clinical drug development, as it might allow monitoring of anti-angiogenic therapy in murine models. We also explored the feasibility of applying the technique for perfusion imaging of mice liver. We observed a low value of interstitial volume fraction and permeability-surface area product in normal mouse liver cases, which corresponded with murine liver physiology and the results previously obtained in the human studies. These results indicated potential for the use of DCE MRI as a biomarker for sinusoidal capillarization and fibrosis in preclinical liver studies. We further implemented the developed DCE MRI technique and analysis method for pre-clinical drug studies with mice implanted with hepatocellular carcinoma xenograft and treated with bevacizumab, a monoclonal antibody which was used in the clinic for anti-angiogenic therapy. Dose-related effects of bevacizumab are observed, suggesting potential of using the technique as a reliable non-destructive testing method for time course observation of microcirculatory changes in animals. This would also facilitate translation and clinical application to early time points after anti-angiogenic therapy, as our current study showed early decrease in micro-vascular density and blood flow after an anti-angiogenic treatment. Finally, we also propose an alternative approach for analyzing DCE-MRI data of necrotic regions based on the diffusional transport of solutes in the tumor interstitium. Gadolinium diffusivity might serve as an alternative interstitial transport parameter in necrotic tumor regions and complement the other microcirculatory parameters derived from DCE MRI for a more complete analysis of the entire tumor.